Repurchase Interest in the Tokopedia Application Based on Application Quality through Satisfaction - Yurindera, Novan (Indonesian Scientific Publication, 2023)
The Covid-19 pandemic has had an impact on various sectors and aspects of life, including the economy and business. On the one hand, the economy is weakening, but on the other hand, the economy is also experiencing improvement, especially in the electronic commerce sector due to the imposed mobility restrictions. The online shopping platform Tokopedia is the leader of the e-commerce or marketplace market in Indonesia in terms of number of visits. This research aims to empirically test the influence of Application Quality consisting of Ease of Use, Information Quality, and Service Interaction Quality of the Tokopedia application on Repurchase Interest through Satisfaction. This analysis uses independent variables, namely Empowerment, Information Quality, and Interaction Quality. The dependent variable is Repurchase Intention, and the intervention variable is Satisfaction. The research method used is quantitative. The population in this research are Tokopedia application users who have made purchases, with a sample of 200 respondents who filled out the questionnaire via Google Form. The statistical method used is Structural Equation Modeling (SEM) using SmartPLS, which consists of outer model analysis, inner model analysis, and continued with hypothesis testing. The research results show that Tokopedia Application Quality has a direct positive influence on Satisfaction, but does not have a direct influence on Repurchase Intention. However, the Quality of the Tokopedia Application has an indirect influence on Repurchase Intention through Satisfaction.